Cost-effectiveness analysis of vaccinations and decision makings on vaccination programmes in Hong Kong: A systematic review. Issue 24 (31st May 2017) - Wong, Carlos K.H.; Liao, Qiuyan; Guo, Vivian Y.W.; Xin, Yiqiao; Lam, Cindy L.K.
Abstract: Objectives: To describe and systematically review the modelling and reporting of cost-effectiveness analysis of vaccination in Hong Kong, and to identify areas for quality enhancement in future cost-effectiveness analyses. Methods: We conducted a comprehensive and systematic review of cost-effectiveness studies related to vaccination and government immunisation programmes in Hong Kong published from 1990 to 2015, through database search of Pubmed, Web of Science, Embase, and OVID Medline. Methodological quality of selected studies was assessed using Consolidated Health Economic Evaluation Reporting Standards checklist (CHEERS). Decision making of vaccination was obtained from Scientific Committee on Vaccine Preventable Diseases (SCVPD) and Department of Health in Hong Kong. Results: Nine eligible studies reporting twelve comparative cost-effectiveness comparisons of vaccination programme for influenza (n = 2), pneumococcal disease (n = 3), influenza plus pneumococcal disease (n = 1), chickenpox (n = 2), Haemophilus influenzae b (n = 1), hepatitis A (n = 1), cervical cancer (n = 1) and rotavirus (n = 1) were identified. Ten comparisons (83.3%) calculated the incremental cost-effectiveness ratio (ICER) of a vaccination strategy versus status quo as outcomes in terms of cost in USD per life-years, cost per quality-adjusted life-years, or cost per disability-adjusted life-years. Among those 10 comparisons in base-case scenario, 4 evaluated interventions were cost-saving relative to status quo while the ICER estimates in 3 of the 6 remaining comparisons were far below commonly accepted threshold and WHO willingness-to-pay threshold, suggestive of very cost-effective. Seven studies were of good quality based on the CHEERS checklist; one was of moderate quality; and one was of excellent quality. The common methodological problems were characterisation of heterogeneity and reporting of study parameters. Conclusions: There was a paucity of cost-effectiveness models evaluating vaccination targeted to the Hong Kong population. All evaluated vaccinations and immunisation interventions in Hong Kong, except for Haemophilus influenzae b, hepatitis A and HPV vaccinations, were considered either cost-saving or very cost-effective when compared to status quo.